2014
DOI: 10.18388/abp.2014_1932
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic profile, adhesive and invasive properties of Candida albicans under the influence of selected plant essential oils.

Abstract: The influence of essential oils (EOs) used at sublethal level, on the presence and intensity of Candida albicans virulence factors was evaluated. Minimal inhibitory concentrations (MICs) of Lemon balm, Citronella, Geranium and Clove oils were established as 0.097% (v/v). Using the agar plates with substrates for proteases, phospholipases and hemolysins it was shown that C. albicans ATCC 10231 and C. albicans ATCC 90028 strains differed in the type and amount of enzymes produced. No significant difference in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 31 publications
(34 reference statements)
2
41
1
1
Order By: Relevance
“…A statistically significant decrease in the adherence of Candida albicans (ATCC 10231) to fibroblasts compared to controls was demonstrated in a study where the organisms were exposed to MIC of essential oils (lemon balm, citronella, geranium clove). However, when the same test was carried out in the presence of half of the CIM, as in this study, their adhesion ability was not significantly affected, which corroborates our results (24). According to Sun et al (11), the resistance of Candida albicans biofilms to the penetration of liquid antimicrobials, including terpinen-4ol, is limited due to its low wettability.…”
Section: Discussionsupporting
confidence: 90%
“…A statistically significant decrease in the adherence of Candida albicans (ATCC 10231) to fibroblasts compared to controls was demonstrated in a study where the organisms were exposed to MIC of essential oils (lemon balm, citronella, geranium clove). However, when the same test was carried out in the presence of half of the CIM, as in this study, their adhesion ability was not significantly affected, which corroborates our results (24). According to Sun et al (11), the resistance of Candida albicans biofilms to the penetration of liquid antimicrobials, including terpinen-4ol, is limited due to its low wettability.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have indeed demonstrated the antimicrobial activity of essential oils from cinnamon and citronella [20,22,30,31]. However, the MIC and MFC values encountered in the present study were lower than those reported by others.…”
Section: Discussioncontrasting
confidence: 78%
“…The surfactants 8–6–8, 8–7–8, 8–8–8, 8–9–8 were tested against the selected microbes for their inhibitory activity using a modified broth microdilution method, as described previously (Budzyńska et al, ; Budzyńska, Sadowska, Więckowska‐Szakiel, & Różalska, ; Yin et al, ). Briefly, serial twofold dilutions of surfactants (concentrations at range: 5.47–10.18 μmol·cm −3 ) were prepared in TSB or RPMI‐1640 media and deposited at volume 100 μL in triplicate in the 96‐well flat‐bottom polystyrene microplates (Nunc, Denmark).…”
Section: Determination Of Minimum Inhibitory Concentrationmentioning
confidence: 99%